Effect of Small Molecule on ex vivo Expansion of Cord Blood Hematopoietic Stem Cells: A Concise Review - Ghafouri-Fard, Soudeh; Niazi, Vahid; Taheri, Mohammad; Basiri, Abbas (Frontiers in Cell and Developmental Biology, 2021)
Hematopoietic stem cells (HSCs) are a group of cells being produced during embryogenesis to preserve the blood system. They might also be differentiated to non-hematopoietic cells, including neural, cardiac and myogenic cells. Therefore, they have vast applications in the treatment of human disorders. Considering the restricted quantities of HSCs in the umbilical cord blood, inadequate mobilization of bone marrow stem cells, and absence of ethnic dissimilarity, ex vivo expansion of these HSCs is an applicable method for obtaining adequate amounts of HSCs. Several molecules such as NR-101, zVADfmk, zLLYfmk, Nicotinamide, Resveratrol, the Copper chelator TEPA, dmPGE2, Garcinol and serotonin have been used in combination of cytokines to expand HSCs ex vivo. The most promising results have been obtained from cocktails that influence multipotency and self-renewal features from different pathways. In the current manuscript, we provide a concise summary of the effects of diverse small molecules on expansion of cord blood HSCs.